Implementasi Storytelling Digital Berbasis Kearifan Lokal untuk Menanamkan Nilai Karakter pada Anak Usia Dini - Samsul Mujtahidin; Laily Fitriani (Universitas Hamzanwadi, 2025)
This study aims to explore the implementation of local wisdom-based digital storytelling as a strategy for character education in early childhood. The research focused on the use of the Riri–Interactive Children’s Story application, which features the legend of Putri Mandalika as a learning medium. The study was conducted at PAUD Mayang Mekar Selong involving 20 children, 3 classroom teachers, and 15 parents. Data were collected through observation, interviews, and documentation, and then analyzed thematically to identify patterns of implementation and children’s responses to the digital media used. The findings revealed significant improvements in three aspects of character development: classroom participation increased from 35% to 70%, expressions of empathy rose from 25% to 65%, and compliance with teachers’ instructions grew from 40% to 75%. Thematic analysis further indicated that digital media enriched with visual and audio elements, combined with locally rooted cultural narratives, successfully attracted children’s attention, enhanced emotional engagement, and strengthened the understanding of moral values such as courage, responsibility, and social care. Moreover, parental involvement played a crucial role in reinforcing the internalization of these values beyond school into daily life at home. These results highlight that local wisdom-based digital storytelling can serve as a relevant, engaging, and contextual learning medium to address the challenges of character education in the digital era.